PROBLEMATIC INTERNET USE DAN PROKRASTINASI AKADEMIK: TANTANGAN MAHASISWA DI ERA DIGITAL - Syaidatu Nugraini Gusnita Halimahtusaddiah; Fara Ulfa; Reni Susanti; Cipto Hadi (Fakultas Psikologi UIN Suska Riau, 2025)
Academic procrastination is one of the common phenomena experienced by undergraduate students. It refers to the habit of delaying academic-related tasks and avoiding actions connected to academic responsibilities. One factor influencing academic procrastination is problematic internet use. This study aims to examine the relationship between problematic internet use and academic procrastination among university students. The sample size in this research consisted of 348 students from Pekanbaru City. Data were collected using the Academic Procrastination Scale (APS) and the Generalized Problematic Internet Use Scale 2 (GPIUS-2). The collected data were analyzed using the Pearson product-moment correlation technique. The results indicate a significant relationship between problematic internet use and academic procrastination, with a correlation coefficient of 0.549 and a significance level of 0.000 (p < 0.000). This means that the higher the level of problematic internet use, the greater the level of academic procrastination, and conversely, the lower the level of problematic internet use, the lower the level of academic procrastination among students.